A 38.4 nW, 1.2 V, 250-Hz, 2nd-Order gm - C LPF With Degenerative SCP Transconductors Achieving 800-mVPP Input Range and 82.1- μVrms IRN for ECG Acquisition - Thanapitak, Surachoke; Pawarangkoon, Prajuab; Surakampontorn, Wanlop; Ahmad, Rafidah; Abdullah Zawawi, Ruhaifi; Manaf, Asrulnizam Abd; Adirek, Suriya; Chanapromma, Chaiyan (My University, 2025)
In this brief, a 2{^{\text {nd} -order gm - C lowpass filter with a practical input linear range of 400mV P dedicated to ECG signal acquisition is proposed. This filter employs a degenerative source-coupled-pair circuit as a gm cell. It enhances the linear input range by a factor of × 4 compared with the source follower filter. Additionally, to mitigate the effect of current source mismatch, a dynamic element matching technique is applied. By doing so, HD2 is suppressed more than 1.5 dB over the entire passband frequency. This proposed filter is implemented in a 0.18 μ m CMOS process. It offers a 250-Hz bandwidth with input-referred noise and a dynamic range of 82.1 μ Vrms and 67.34 dB, respectively. The power consumption of 38.4 nW is achieved with a 1.2 V supply. Compared with other recent nano-power filters, the proposed filter provides the highest linear input range with competitive Figure-of-Merit to the top-tier designs. It is therefore beneficial to the practical implementation of a low-power ECG acquisition system.
Keywords: Biopotential acquisition; ECG; gm-C filter; heart; low-power; lowpass filter; MOS; nano-power; transconductor